Effects of the encapsulation of Lactobacillus acidophilus and Spirulina platensis on carcass yield and meat quality of broilers under heat stress conditions - Zahra Ranjbarinasab; Mozhgan Mazhari; Omidali Esmaeilipour; Fatemeh Shahdadi; Arsalan Barazandeh (Spanish Journal of Agricultural Research, 2024)
Aim of study: To evaluate the effects of adding Lactobacillus acidophilus (LA), Spirulina platensis (SP) and the encapsulation of LA on the relative weights of carcass parts and meat quality of broilers subjected to heat stress.